Cork oak woodlands patchiness: A signature of imminent deforestation? - Costa, Augusta; Madeira, Manuel; Plieninger, Tobias (Applied Geography, 2014)
The cork oak (Quercus suber L.) woodlands of the agroforestry landscapes of Southwestern Iberia are undergoing drastic change due to severe natural and anthropogenic disturbances. These may eventually result in woodland loss or deforestation, the final step of an ongoing process of woodland degradation. Monitoring changes in the spatial patterns of woodlands – especially fractional canopy cover of woodlands and/or their patchiness in the landscape mosaic – potentially enables forecasting of loss and responding to it at an early stage. We examine the degradation process in two cork oak woodlands, resulting from distinct disturbances, wildfire and oak mortality, aimed at evaluating the changes, trends and deviations of the spatial attributes of these woodlands as they move from an initial (less disturbed ecosystem) to a final state (more disturbed ecosystem). While undergoing disturbances, both woodlands exhibited similar trends of decreasing fractional canopy cover and decreasing number of larger patches. Patchiness rather than fractional canopy cover seems, however, to be potentially more useful as a signature of imminent oak woodlands deforestation, given that its contrast before and after disturbance was much higher. The structural dynamics of oak woodlands is a crucial but neglected issue that needs greater attention from policy forums working toward their conservation and restoration as well as from stakeholders and society as a whole.
Keywords: Forest degradation; Fractional canopy cover; mediterranean landscape; Patch size–frequency distribution; Power-law function; Quercus suber L.